The 60s in the 21st Century. Imagining the Region from/in Latin America (Anclajes, 2024)
This text offers a review of the ideas of region in four theoretical-critical tours produced at the intersection between literary criticism, anthropology and sociology: The Americas and Civilization by Darcy Ribeiro, Writing across Cultures: Narrative Transculturation in Latin America by Ángel Rama, Literatura y subdesarrollo and El Paraná y su expresión literaria by Adolfo Prieto. We approach these notions by considering the intellectual connections between their authors, in order to contextualize them within the socio-cultural context of the 1960s and to ask how the propositions of Latin American cultural regions might endure today. The formation of a university geopolitical framework enables cross-border dialogue around this shared issue. Thus, the modern national project is addressed by formulating literary expressions that incorporate elements of popular culture, with the aim of understanding their formative process and developmental challenges, while also envisioning alternative possible mappings.
Keywords: Region; Latin America; Ángel Rama; Darcy Ribeiro; Adolfo Prieto